Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2013)
Random events can create patterns. Texts with totally independent origin may give rise to transverse reflections. This introduction is not a presentation of the individual article on its own merits, but rather a presentation of reflections that the articles raise. The individual articles are introduced in the abstracts that initiate the articles. In the introduction to the last issue of the journal (13/3) Jan Karlsson warns against blind faith in the basic assumptions of the Nordic working life research. One example is the uncritical belief in autonomy at work as a means for better productivity and better quality of working life, which can be misleading. This issue is, however, not an uncritical celebration of Nordic working life and the values behind. On the contrary, there is one visible thread that goes through the five articles presented in this issue that can be expressed as follows: “It could have been so nice, but it is actually quite bad.” All the articles demonstrate how difficult it is to realize basic values of Nordic working life at the micro-level. Yet, they also to a certain extent point at options to restore these values (...)